Riscos de deslizamentos e inundações e condições de moradia em aglomerados subnormais na bacia do rio Sanhauá: avaliação e análise integrada - Nascimento, Maria Odete Teixeira do (2009)
The problems of the areas of risk disaster in Brazilian cities, especially the environmental risks of geological and geotechnical character, such as landslides, and hydrometeorological such as floods, are often related to socioeconomic and environmental determinants. Thus, the subnormal agglomerations (slums) are situated in areas with major problems in several aspects, since they are usually subject to high levels of environmental risks due to occupation of unsuitable areas, driven by the exclusive real estate market. Therefore, the search for methodologies that cover the vicissitudes of the dynamics of the urban environment is essential to optimize actions that minimize this problem. Thus, this work analyzes social risks, including geological and geotechnical components in addition to hydrometeorological data, together with social indicators of housing conditions in subnormal agglomerations: Saturnino de Brito, Renascer I, and Santa Emília de Rodat, situated in the basin of Sanhauá river in João Pessoa, Paraíba State. It proposes a methodology for priorizing actions to improve housing or home reallocations. Regarding to the determination of environmental risks indices we used the methodology proposed by the Ministério das Cidades (Brazil, [2006]). For determination of housing conditions, we used the methodology developed by Silva (2006), focused on the indicator of living conditions which covers subindicators of density and housing quality. The analyse of the results included an integrated multiobjective methodology whic h makes use of a two-dimensional representation of the field of possible solutions of indicators obtained that describes together housing conditions and risk variables, based on integrated environmental methodology of hydrographical basins used by UNESCO (1987). Its is concluded that the agglomerations have low levels of risk in their majority, while in some areas, especially in Saturnino de Brito agglomeration, there was observed higher frequency of high and very high levels of occurrence of geological and geotechnical disaster. The greatest risks of flooding, classified as high, were detected only in the Santa Emília Rodat agglomerate. Regarding to the housing conditions in this agglomeration we observed that the majority of dwellings are classified as midst salubrious. The integrated analysis of the studied sample indicated that for most groups of households it is more relevant the reallocation instead of improvements of housing.